Modeling Cell-Cell Interactions in Parkinson’s Disease Using Human Stem Cell-Based Models - Simmnacher, Katrin; Lanfer, Jonas; Rizo, Tania; Kaindl, Johanna; Winner, Beate (Frontiers in Cellular Neuroscience, 2020)
Parkinson disease (PD) is the most frequently occurring movement disorder, with an increasing incidence due to an aging population. For many years, the post-mortem brain was regarded as the gold standard for the analysis of the human pathology of this disease. However, modern stem cell technologies, including the analysis of patient specific neurons and glial cells, have opened up new avenues for dissecting the pathologic mechanisms of PD. Most data on morphological changes, such as cell death or changes in neurite complexity, or functional deficits were acquired in 2D and few in 3D models. This review will examine the prerequisites for human disease modeling in PD, covering the generation of midbrain neurons, 3D organoid midbrain models, the selection of controls including genetically engineered lines, and the study of cell-cell interactions. We will present major disease phenotypes in human in vitro models of PD, focusing on those phenotypes that have been detected in genetic and sporadic PD models. An additional point covered in this review will be the use of iPSC-derived technologies to model cell-cell interactions in PD.